HUBUNGAN PARAMETER KEBUGARAN FISIK DENGAN SINDROMA FRAILTY PADA LANSIA DI JAKARTA - Rayner Abdiwijaya Hariyanto; Linda Suryakusuma; Yvonne Suzy Handajani; Yuda Turana (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2026)
Introduction: Frailty is a multifactorial geriatric syndrome resulting from the loss of the body's ability to cope with stressors due to aging. According to a study conducted by Asenso et al., the global prevalence of frailty is 13.6%. Aim: This study is aimed to understand the relationship between physical fitness parameters and frailty syndrome in the elderly. Methods: This study uses a cross-sectional involving 98 respondents aged 60 years and above. ADL was measured using the Barthel Index. Balance was measured using the Berg Balance Scale. Physical activity was measured using the SQUASH questionnaire with cutoffs based on the GPAQ. Frailty status was assessed using the Fried frailty phenotype. Results: From 98 respondents, the majority were female (71.4%), aged 60-74 years (74.5%), with a higher education level (51%). A total of 18.4% of the elderly experienced frailty. Chi-square analysis showed that significant factors were age (p<0.001; OR: 7.408), ADL (p=0.019; OR: 3.944), Balance (p=0.042; OR: 7,800), and physical activity (p=0.014; OR: 3.714). Multiple logistic regression showed that age is the most influential factor in frailty (p=0.002; OR: 6,209) and followed by physical activity (p=0.030; OR: 3.834). Discussion: Age, ADL, balance, and physical activity were found to have a significant relationship with frailty. Among these factors, age was identified as the most influencing factor. Keywords: ADL, age, balance, elderly, frailty, physical activity